Development of novel ultra-sensitive IL-11 target engagement assays to support mechanistic PK/PD modeling for an anti-IL-11 antibody therapeutic. Issue 1 (31st December 2022) - Myzithras, Maria; Lin, Siqi; Radden, Legairre; Hess Kenny, Cynthia; Cai, Zheng; MacDonald, Angus; Binetti, Ralph; Marlow, Michael; Fracasso, Paul; Gibson, Glenn; Bartlett, Christina; Hawkins, Julie; et al.
ABSTRACT: An in-house antibody generation campaign identified a diverse, high affinity set of anti-interleukin-11 (IL-11) monoclonal antibodies (mAbs) to enable successful development of novel, custom ultra-sensitive target engagement assays for detection of "free" (unbound to the dosed anti-IL-11 therapeutic mAb) and "total" (free and mAb-IL-11 complexed form) IL-11 in preclinical species and human. Antibody hits from distinct epitope communities were screened on various platforms, including enzyme-linked immunosorbent assay, Meso Scale Discovery, Simoa HD-1 and Simoa Planar Array (SP-X), and used for assay development and sensitivity optimization. The ultra-sensitive SP-X format achieved a lower limit of quantitation of 0.006 pg/mL, enabling the first reported baseline levels of IL-11 in healthy control plasma determined by custom bioanalytical assays. These newly established baseline levels supported mechanistic pharmacokinetic/pharmacodynamic modeling in mouse, cynomolgus monkey, and human for a greater understanding of preclinical study design and in vivo dynamic interaction of soluble IL-11 with an anti-IL-11 antibody therapeutic candidate. Modeling and simulation also helped refine the utility of assays with respect to their potential use as target engagement biomarkers in the clinic. Abbreviations IL-11: Interleukin-11, TE: Target engagement, PK/PD: Pharmacokinetic/pharmacodynamic, mAb: Monoclonal antibody, NHP: Non-human primate, IgG: Immunoglobulin G, Cyno: Cynomolgulus monkey, GFR: Glomerular filtration rate, BQL: Below quantitation levels, DRM: Disease relevant model, kDa: kilodaltons, SPR: Surface plasmon resonance, pSTAT3: phosphorylated STAT3, IL-11R: Interleukin-11 receptor, TPP: Target product protein, LLOQ: Lower limit of quantitation, RLU: Relative light units